Associations Between Knowledge, Attitude and Behavior With Helminthiasis in Children - Agnesia Alyssa; Dewi Saputri (Sumatera Medical Journal, 2024)
Background: Soil-transmitted helminths (STH) infection is currently one of the highest prevalence neglected tropical diseases in children. Factors contributing to such case are children’s hygiene, as well as the existence of helminths in the surrounding soil. Objective: Therefore, this research is done to determine whether there is significant association between hygiene and STH infection in children. Methods: This observational analysis with a cross-sectional design was conducted on elementary school children by interviewing the children and obtaining fecal samples. Results: Analysis of 197 fecal samples shows that 14.7% of the children were infected with STH and results of the interview show more children had poor knowledge about STH infection (69%). Good hygiene attitude and behavior were found in the majority of the subjects (58.9% and 81.7% respectively). The chi-square analysis performed shows no significant relation between knowledge (p=0.626), attitude (p=0.975), and behavior (p=0.376) and the incidence of STH infection. Conclusion: In this study, although children demonstrated poor knowledge of STH infection but had good hygiene attitudes and behaviors, there was no significant link between these factors and STH infection. This emphasizes the need for ongoing hygiene education in elementary school children.